2017
DOI: 10.4314/jae.v21i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Control Methods for Parasites among Pastoralists Communities in Adamawa State, Nigeria

Abstract: The study analyzed the indigenous control methods of livestock parasites by pastoralists' communities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This implies that, the prevalent nature associated with these parasites could create high awareness of cattle parasites in the study area which could also trigger the pastoralist to acquire for more knowledge on the cause and management of these parasites. This is in agreement with the findings of Grange et al (2014); Siddiqi and Ashraf (2016); Robert et al (2016); Usman et al (2017); Lemy and Egwunyenga (2018) all reported that Tape worms, Ticks and Flies were common parasites extremely been aware of by pastoralists.…”
Section: Level Of Awareness On Cattle Parasitessupporting
confidence: 89%
See 1 more Smart Citation
“…This implies that, the prevalent nature associated with these parasites could create high awareness of cattle parasites in the study area which could also trigger the pastoralist to acquire for more knowledge on the cause and management of these parasites. This is in agreement with the findings of Grange et al (2014); Siddiqi and Ashraf (2016); Robert et al (2016); Usman et al (2017); Lemy and Egwunyenga (2018) all reported that Tape worms, Ticks and Flies were common parasites extremely been aware of by pastoralists.…”
Section: Level Of Awareness On Cattle Parasitessupporting
confidence: 89%
“…(2016);Scasta (2016); Ola-Fadunsin (2017);Usman et al (2017); Ola-Fadunsinet al (2020), who reported that Tapeworms, lice and flies were highly prevalent cattle parasite found in herds as such are well known by pastoralists in Nigeria.…”
mentioning
confidence: 99%
“…It sustains the employment and income of millions of people in rural areas and generates animal power and organic manure for arable farming mainly in the sudano-sahalian ecological zones of the country. The sale of cattle and cattle products provides the major source of cash income to the pastoralists for the purchase of consumer goods (Usman et al, 2017). Over 90% of the country's cattle are owned and herded by the Fulani pastoralists, most of whom are nomadic, semi-settled or trans-human (Ikhatua, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These practices remain relevant despite the advancement of modern veterinary medicine particularly in rural areas (Mafimisebi et al, 2012). The knowledge is used to provide economical solutions to improve productivity of animals and reduction in poverty of the poor farmers (Usman et al, 2017). The practices are designed for either therapeutic or prophylactic use in cattle diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation